Quantifying Greenhouse Gas Emissions Attributable to Smallholder Livestock Systems in Western Kenya: Cradle to Farm Gate Life Cycle Assessment - Ndung'u, Phyllis W.; Takahashi, T.; Toit, C.J.L. du; Robertson-Dean, M.; Butterbach-Bahl, Klaus; McAuliffe, G.; Merbold, Lutz; Goopy, John P. (International Livestock Research Institute, 2021)
Ruminants are central to the economic and nutritional life of much of sub-Saharan Africa, but cattle are now blamed for having disproportionately large negative environmental impact through (amongst other things) emissions of greenhouse gases. However, the exact mechanism behind these emissions is not well-understood and indeed accurate estimates themselves are lacking due to a paucity of reliable data. Employing individual animal records obtained at regular farm visits, this study quantified emissions intensities (EIs) of smallholder farms in three counties of Western Kenya through life cycle assessment (LCA). Crude protein (CP) was chosen as the functional unit to capture outputs of both milk and meat. The results showed that milk is responsible for 80-85% of total CP output. Farm EI ranged widely from 20- > 1,000 kg CO2-eq/kg CP and median EIs were 60, 71 and 90 kg CO2-eq/kg CP for Nandi, Bomet and Nyando respectively. EIs referenced to milk alone revealed that while the median EI for Western Kenya (2.3 kg CO2-eq/kg milk) was almost twice that reported for Europe, up to 50% of farms had EIs comparable to the mean Pan- European EIs. Enteric CH4 contributed > 95% of emissions and manure ~4%, with negligible emissions attributed to input to the production system. Collecting data from individual animals on smallholder farms enabled the demonstration of an extremely heterogenous EI environment amongst smallholder farms and provides clear indicators on how to achieve low EIs in these environments. Contrary to some current belief, our data show that industrial- style intensification isn't required to achieve low EI, and that this can be achieved in a low input environment. Enteric CH4 production overwhelmingly drives farm emissions in these systems and, as this is strongly collinear with nutrition and intake, effort will be required to achieving an 'efficient frontier' between feed, emissions and animal productivity.